Chapter 15 Brain Tumors and the Lynch Syndrome - Peltomäki, Päivi (InTechOpen, 2011)
Lynch syndrome (LS) (MIM No. 120435-6), previously known as hereditary nonpolyposis colorectal cancer (HNPCC) (Boland, 2005), is an autosomal dominant disorder caused by germline mutation in one of the DNA mismatch repair (MMR) genes. LS is among the most prevalent cancer syndromes in man and is estimated to account for 1-6% of all colorectal cancers (Lynch & de la Chapelle, 2003).